FOREWORD - Van Harte, E.L. (Scientia Militaria - South African Journal of Military Studies, 2011)
Scientia Militaria: the South African Journal of Military Studies, initially known asMilitaria:Periodical for Military History, was published for the first time in 1969 bythe Military Archives, but through negotiations between the faculty at the MilitaryAcademy and the Director of the Military Archives the Journal found a new home inthe Faculty of Military Science in January 1997. Several committed academicsserved as editors, including the likes of Deon Visser, Ian van der Waag, TheoNeethling and Francois Vreÿ. They and many others before 1997 sustained thepublication of this journal over the last 40 years. To all of those who havecontributed to the sustainability of the journal, be it through the writing of articles,the securing of funds, or by serving on the editorial board, we express our greatestappreciation for making sure that Scientia Militaria could appear as a biannualjournal.